2022
DOI: 10.1007/s11060-022-04001-y
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Frailty Scale as predictor of overall survival after resection of high-grade glioma

Abstract: Background The Clinical Frailty Scale (CFS) describes the general level of fitness or frailty and is widely used in geriatric medicine, intensive care and orthopaedic surgery. This study was conducted to analyze, whether CFS could be used for patients with high-grade glioma. Methods Patients harboring high-grade gliomas, undergoing first resection at our center between 2015 and 2020 were retrospectively evaluated. Patients’ performance was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 27 publications
1
12
1
Order By: Relevance
“…However, this is the first study focussing specifically on its use in oncology and haemato‐oncology inpatients (Church et al, 2020 ). Unlike other oncology studies, we found a relatively weak correlation between CFS and PS, and PS did not independently predict survival (Klingenschmid et al, 2022 ; Shah et al, 2022 ). This highlights the challenge of assessing PS in the inpatient setting, where patients may have limited opportunities for mobilisation and self‐care, and rapid changes in physiology and function can occur.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, this is the first study focussing specifically on its use in oncology and haemato‐oncology inpatients (Church et al, 2020 ). Unlike other oncology studies, we found a relatively weak correlation between CFS and PS, and PS did not independently predict survival (Klingenschmid et al, 2022 ; Shah et al, 2022 ). This highlights the challenge of assessing PS in the inpatient setting, where patients may have limited opportunities for mobilisation and self‐care, and rapid changes in physiology and function can occur.…”
Section: Discussioncontrasting
confidence: 99%
“…Frailty is an increasingly commonly used construct in modern healthcare. Our study supports the use of the CFS in oncology and haematology (Klingenschmid et al, 2022 ; Shah et al, 2022 ; Wall et al, 2021 ) . Recognising the implications of frailty may help healthcare professionals discuss the risks and benefits of potential treatments with patients and their families.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Nowadays, biological but not chronological age in combination with frailty have more impact on the decision making in cases of malignant glioma [ 16 , 17 ]. Thus, our center generally offers aggressive tumor resection and concomitant radio-chemotherapy to elderly patients with low frailty.…”
Section: Introductionmentioning
confidence: 99%